4a - 5 = 7a - 7
-5 = 3a - 7
2 = 3a
a = 3/2
Chat with our AI personalities
a=5
4a - 5b = 74a +5b = 17From the first equation:4a = 7 + 5bsubstitute this value in the second equation:7 + 5b + 5b = 177 + 10b = 1710b = 10b = 1Now,solve for a :4a - 5(1) = 74a = 7 + 54a = 12a = 3
(7a + 35)/-7 = 7(a + 5)/-7 = -(a + 5) = (-a - 5)
3a + 4a +/- 6; take the 3a & 4a and combine them; 7a +/- 6 would be your answer as 6 cannot combine with 7a due to the variable. If 7a +/- 6 = 0, then subtract/add (respectively) the 6 depending on the operation. Therefore 7a + 6 = 0 turns to 7a = -6. Divide the 7 with the -6 to get the a alone; a = -6/7 or -0.8. Cannot be simplified.
a2 + 7a - 8a2 = 6a7 ∴ a2 + 7a - 8a2- 6a7 = 0 ∴ a + 7 - 8a - 6a6 = 0 ∴ 7 - 7a - 6a6 = 0 ∴ 6a6 + 7a - 7 = 0